2022
DOI: 10.3390/s22134717
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Driving Detection Method Based on Combination of BP Neural Network and Time Cumulative Effect

Abstract: Fatigue driving has always received a lot of attention, but few studies have focused on the fact that human fatigue is a cumulative process over time, and there are no models available to reflect this phenomenon. Furthermore, the problem of incorrect detection due to facial expression is still not well addressed. In this article, a model based on BP neural network and time cumulative effect was proposed to solve these problems. Experimental data were used to carry out this work and validate the proposed method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…Arefnezhad et al [33] have presented a study of risk of fatigueness during automated driving and used difference of PERCLOS for analyzing the proportion of eye closure in order to determine driver's fatigueness. Adoption of eye closure is also reported in work of Dzuida et al [34] and Shang et al [35] while similar trend of work is also reported by Chen et al [36] where facial detection is initially carried out using Adaboost while tracing of facial movement is done by Kalman filter. Further facial landmarks were detected using regression tree of cascaded form followed by using backpropagation neural network for training.…”
Section: Existing Studies Towards Driver's Fatiguenesssupporting
confidence: 63%
“…Arefnezhad et al [33] have presented a study of risk of fatigueness during automated driving and used difference of PERCLOS for analyzing the proportion of eye closure in order to determine driver's fatigueness. Adoption of eye closure is also reported in work of Dzuida et al [34] and Shang et al [35] while similar trend of work is also reported by Chen et al [36] where facial detection is initially carried out using Adaboost while tracing of facial movement is done by Kalman filter. Further facial landmarks were detected using regression tree of cascaded form followed by using backpropagation neural network for training.…”
Section: Existing Studies Towards Driver's Fatiguenesssupporting
confidence: 63%
“…The accuracy of the proposed model with facial expressions increased by 8.4%. The proposed model can filter out artifacts caused due to facial expressions while detecting driver fatigue [33]. Furthermore, Li, Y. et al proposed a lightweight wearable device based upon a convolution neural network for detecting driver fatigue through eye images [34].…”
Section: Recent Literature Review Based Upon Modern Techniquesmentioning
confidence: 99%
“…When these features appeared, the driver may enter a state of mild or severe fatigue. The experiments were measured simultaneously to find the relationship between the facial and physiological states over time [12]. Since the human head may oscillate while driving due to observation of the rearview mirror and reversing mirror, the method of fixing the camera may cause the measurement to be missed.…”
Section: Driver Face Status Monitoringmentioning
confidence: 99%